Global approaches to affordable housing: comparative insights from developed and developing countries and the case of Palestine - Sabah, Faisal Yousef (Frontiers in Built Environment, 2025)
Affordable housing remains one of the most pressing global policy challenges, with strategies and constraints differing significantly between developed and developing contexts. This study employs a comparative policy analysis of six case countries United States, Germany, Japan, India, Brazil, and South Africa to examine how diverse socio-economic and political settings shape housing strategies. The analysis focuses on key factors influencing affordability, including regulatory frameworks, financial mechanisms, community participation, and innovation in addressing local needs. In Palestine, the interaction of political conflict, land restrictions, and economic constraints creates a unique and highly constrained housing environment that requires context-specific responses. The study indicates that developed countries benefit from structured public–private partnerships and robust regulatory frameworks, whereas developing countries rely more on community-driven initiatives and flexible financing models. Lessons from this comparative analysis can inform global policymakers by emphasizing resilience, inclusivity, and sustainability in housing policies, with particular relevance for improving affordability in conflict-affected and economically constrained settings such as Palestine.